PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 001 BAGAN KOTA BAGANSIAPIAPI - Wahyun, Desi Wahyun Desi; Antosa, Zariul Anto Zariul; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research was motivated by the low student learning outcomes in mathematics. From the daily tests carried only 13 students who have mastery (52%) whereas those who did not complete 12 (48%) with KKM 65 While the average student learning outcomes is 64.0. The form of this research is a form of Classroom Action Research (CAR), which aims to improve the learning outcomes of mathematics with application of cooperative learning model TSTS the fourth grade students of SD Negeri 001 Bagansiapiapi Rokan Hilir with material fractions. The problem of this study are Is the application of cooperative learning model to improve learning outcomes TSTS math fourth grade students of SD Negeri 001 Bagansiapiapi Rokan Hilir. The subjects were fourth grade students of SD Negeri 001 Bagansiapiapi the number of students 25 people consisting of 13 male students and 12 female students. This study presents the results obtained by studying the occurrence of an increase in the number of students who reach the KKM. On the basis of scores of students who achieve a KKM 13 people (52%), daily tests first 14 people (58%) and the second daily test increased to 22 people (88%). The average increase learning outcomes of the basic score is 64.0, while the average of the first UH student learning outcomes increased to 78.4, the average of the second UH student learning outcomes also increased to 85.2. Analysis of the observation sheet activities of teachers and students on the application of cooperative learning model TSTS first cycle and second cycle. For all teachers at the first meeting of the percentage by 57% (2.28), the second meeting 78% (3.14), the third meeting of 82% (3.28) and the fourth meeting of 100% (4.0). For a student activity at the first meeting by 53% (2.14), at the second meeting by 75% (3.0), the third meeting of 82% (3.28) and the fourth meeting of 100% (4.0). Keyword : Cooperative Learning Model, Type Two Stay Two Stray (TSTS), Mathematics Learning Outcomes